Irisin attenuates cardiac injury and improves prognosis in rats with hemorrhagic shock by maintaining mitochondrial homeostasis via the AMPK/Drp1 pathway - Zhang, Zheng; Zhang, Yufang; Zou, Xiaofang; Li, Jiake; Chi, Yunfei; Bai, Hailiang; Wei, Bin; Yun, Huiting; Zhang, Quanxi; Cao, Weihua; Liu, Haiyan; Duan, Hongjie (Frontiers in Pharmacology, 2025)
ObjectiveHemorrhagic shock (HS) is a critical clinical condition in which cardiac dysfunction and failure are leading causes of mortality. Mitochondrial dysfunction is central to the pathogenesis of cardiac dysfunction in HS. Irisin has been shown to improve mitochondrial function and protect against ischemia-reperfusion injury (IRI), but its specific effects on myocardial injury in HS are unknown. This study investigates irisin’s therapeutic potential in a rat model of HS.MethodsFor in vivo studies, a rat HS model was established via controlled blood withdrawal and Animals were allocated to four groups: Sham, HS, HS + Vehicle (HS + Veh), and HS + Irisin. Physiological responses were evaluated through temporal sampling at 1, 3, and 6 h post-HS. For in vitro studies, H9c2 cardiomyocytes were exposed to oxygen-glucose deprivation to establish a hypoxic model. Cells were categorized into six groups: normoxia (N), normoxia + AMPK inhibitor compound C (N + Cc), hypoxia (H), hypoxia + Cc (H + Cc), hypoxia + irisin (H + Irisin), and hypoxia + Cc + irisin (H + Cc + Irisin). Cellular functional outcomes were analyzed following 3-h hypoxia exposure.ResultsHS significantly reduced serum irisin levels. Exogenous irisin administration enhanced survival rates, stabilized mean arterial pressure (MAP), lowered lactate (LAC) levels, improved cardiac structure and function, and reduced myocardial injury biomarkers in HS rats. Mechanistically, irisin activated AMP-activated protein kinase (AMPK) and Sirtuin 1(SIRT1), to suppress the expression of dynamin-related protein 1 (Drp1) and fission protein 1 (Fis1), while upregulating mitofusin 1 (Mfn1). This modulation of mitochondrial dynamics preserved cardiomyocyte mitochondrial membrane potential (MMP), ATP production, and structural integrity. Hypoxic H9c2 cardiomyocytes exhibited consistent results. To confirm AMPK/Drp1-dependent mechanisms, Cc was administered to inhibit irisin-induced AMPK activation. Cc abolished irisin’s suppression of Drp1/Fis1 and its Mfn1 upregulation. Furthermore, Cc eliminated irisin-mediated protection in both H9c2 cardiomyocytes and mitochondria.ConclusionOur study demonstrates that irisin ameliorates cardiac function and enhances early prognosis in HS. These cardioprotective effects are achieved through attenuation of myocardial damage and SIRT1/AMPK/Drp1 pathway-dependent restoration of mitochondrial homeostasis.